Ten questions concerning the paradox of minimizing airborne transmission of infectious aerosols in densely occupied spaces via sustainable ventilation and other strategies in hot and humid climates. (15th April 2022) - Ghaddar, Nesreen; Ghali, Kamel
Abstract: Airborne disease transmission in indoor spaces and resulting cross-contamination has been a topic of broad concern for years – especially recently with the outbreak of COVID-19. Global recommendations on this matter consist of increasing the outdoor air supply in the aim of diluting the indoor air. Nonetheless, a paradoxical relationship has risen between increasing amount of outdoor air and its impact on increased energy consumption – especially densely occupied spaces. The paradox is more critical in hot and humid climates, where large amounts of energy are required for the conditioning of the outdoor air. Therefore, many literature studies investigated new strategies for the mitigation of cross-contamination with little-to-no additional cost of energy. These strategies mainly consist of the dilution and/or the capture and removal of contaminants at the levels of macroenvironment room air and occupant-adjacent microenvironment. On the macroenvironment level, the dilution occurs by the supply of large amounts of outdoor air in a sustainable way using passive cooling systems, and the removal of contaminants happens via filtering. Similarly, the microenvironment of the occupant can be diluted using localized ventilation techniques, and contaminants can be captured and removed by direct exhaust near the source of contamination. Thus, this work answers ten questions that explore the most prevailing technologies from the above-mentioned fronts that are used to mitigate cross-contamination in densely occupied spaces located in hot and humid climates at minimal energy consumption. The paper establishes a basis for future work and insights for new research directives for macro and microenvironment approaches. Graphical abstract: Image 1 Highlights: - There is a need to mitigate airborne transmission of infectious aerosols in densely occupied spaces - Contaminant removal strategies at macroenvironment and microenvironment by dilution and/or capture are investigated - Reducing outdoor air intake while cleaning indoor air is an attractive method to provide improved air quality at reduced energy cost - The implementation of localized air distribution systems should be practical for densely occupied spaces - Future research should focus on smart strategies for microenvironment ventilation & disinfecting clothing